2017
DOI: 10.1080/21645515.2016.1263409
|View full text |Cite
|
Sign up to set email alerts
|

A reflection on invasive pneumococcal disease and pneumococcal conjugate vaccination coverage in children in Southern Europe (2009–2016)

Abstract: Higher-valent pneumococcal conjugate vaccines (PCVs) were licensed from 2009 in Europe; similar worldwide clinical effectiveness was observed for PCVs in routine use. Despite a proven medical need, PCV vaccination in Southern Europe remained suboptimal until 2015/16.We searched PubMed for manuscripts published between 2009 and mid-2016. Included manuscripts had to contain data about invasive pneumococcal disease (IPD) incidence, or vaccination coverage with higher-valent PCVs. This review represents the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 36 publications
1
7
0
1
Order By: Relevance
“…The cancer prevention message most discernably promoted with HPV vaccination was widely recognized across interviewees, but was not universally convincing as some parents considered the likelihood of HPV vaccine-preventable cancer remote in their adolescent child (overall and in light of regular cancer screenings such as pap smears). This theme was generally consistent with at least two prior studies as well, where parents voiced limited concern about their adolescents’ susceptibility to HPV infection [ 9 , 13 ]. One parent who refused the HPV vaccine for her daughter also considered the cervical cancer risk a worthwhile deterrent to unsafe sexual practices.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The cancer prevention message most discernably promoted with HPV vaccination was widely recognized across interviewees, but was not universally convincing as some parents considered the likelihood of HPV vaccine-preventable cancer remote in their adolescent child (overall and in light of regular cancer screenings such as pap smears). This theme was generally consistent with at least two prior studies as well, where parents voiced limited concern about their adolescents’ susceptibility to HPV infection [ 9 , 13 ]. One parent who refused the HPV vaccine for her daughter also considered the cervical cancer risk a worthwhile deterrent to unsafe sexual practices.…”
Section: Discussionsupporting
confidence: 85%
“…It was clear from our interviews, as in other prior investigations [ 7 , 9 , 13 , 23 ], that parents often look to their healthcare provider for advice about the HPV vaccine and this informs their attitudes. But this educational burden may be more nuanced than previously appreciated.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…It has been reported that approximately 1 million people die of pneumococcal diseases annually, most of whom are children under 5 years old [24]. Pneumococcal conjugate vaccines (PCVs) targeting 7, 10, or 13 of more than 90 serotypes of S. pneumoniae have been successively introduced to reduce the burden of invasive pneumococcal disease (IPD) in vaccinated children in developed countries [5, 6]. In fact, it has been reported that after licensing PCV13, pneumococcal diseases of any cause, but especially those caused by PCV13 minus PCV7 serotypes, were further decreased across each age group in the UK [7].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, each country has implemented the vaccine in different manners and at various times across the last decade. In Spain, Italy, and Canada, there is a national recommendation for PCV in children, but implementation is on a regional basis as compared to national implementation, and in Spain a PCV NIP was not introduced until 2015/2016 with low PCV13 uptake until recent years [ 62 ]. Additionally, in some countries where multiple vaccines are used in clinical practice (i.e., Canada, Germany, Italy, South Korea, and Sweden), there may be suboptimal overall protection of all vaccine serotypes at a national level.…”
Section: Discussionmentioning
confidence: 99%